Greedy in Thailand film by Pascal Vasselin - Vasselin, Pascal (Australia : BBC, 2002)
In July 1997, the biggest speculative bubble ever burst. After years of enjoying the fruits of the prosperous global markets, particularly those in Asia, investors the world over had to face up to the crash. This documentary takes a look at what caused the crash, providing an in-depth examination of the root causes of the crisis by crossing the interviews of both Thai and international bankers and speculators
Title from title screen
Executive producer, Christine Camdessus
Narrated by Nick Fraser
DVD format
Keywords: Financial crises -- Asia; International finance; Thailand -- Economic conditions